A comprehensive immune repertoire signature distinguishes pulmonary infiltration in SARS-CoV-2 Omicron variant infection - Li, Xuechuan; Zhu, Hongyi; Xu, Peipei; Zhang, Jie; Wang, Zhe; He, Hui; Shen, Fang; Jiang, Yi; Shen, Lijuan; Xiang, Jing; Yang, Linhua; Yang, Chao; et al. (Frontiers in Immunology, 2024)
IntroductionThe coronavirus disease 2019 (COVID-19) global pandemic has been the most severe public health emergency since 2019. Currently, the Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been the most dominant. The most prominent symptom of SARS-CoV-2 infection is respiratory. Meanwhile, the fatality of COVID-19 was mainly from pneumonia. However ,in patients with SARS-CoV-2 infection who have pneumonia and those who do not, the differences in the immune repertoire still require further investigation.MethodsWe conducted seven-chain adaptome immune repertoire analyses on patients with SARS-CoV-2 Omicron infection, both with and without pulmonary infiltration.ResultsPatients with pulmonary infiltration exhibit lymphopenia, a decreased proportion of the overall TCR repertoire alongside an increased BCR repertoire, reduced IGHD and IGHM isotype expression, a shorter mean CDR3 length for TRG, and a longer mean length for TRD, as well as diminished clonality and diversity in the TCR/BCR repertoire. Meanwhile, patients with pulmonary infiltration have distinct V-J gene usage and unique CDR3 signature, as well as BCR class switch recombination pattern. Finally, prior vaccination triggered less BCR IGHM/IGHD somatic hypermutation response, preserved the diversity of the entire adaptive immune repertoire, and provided clinical protection against severe or critical conditions following Omicron infection.DiscussionWe report a unique, comprehensive adaptive immune system signature in patients with pulmonary infiltration, which may serve as potential immunological biomarkers and therapeutic targets.